Challenges for Novice Developers in Rough Terrain Rescue Robots: A Survey on Motion Control Systems - Branesh M. Pillai; Jackrit Suthakorn (Journal of Control Science and Engineering)
Several researchers have revealed the huge potentials of rescue robots in disaster zones. In addition to searching for victims, these intelligent machines are also effective in obtaining useful information from the zones. These functions help to optimize the search and rescue missions. However, the fact that rescue robots have to operate in risky and dangerous environments necessitates the need for such machines to have an efficient motion control system, which can help them to operate autonomously or with minimal human control. This paper reviews the use of reliable controllers in enhancing the sensing capabilities of rescue robots. Huge potential of sensorless sensing method in the rescue robots are highlighted. It is shown that the use of sensorless sensing method enables developer to create simple and cheaper robots for various complex situations. Thus, it is imperative to conduct further studies on how to optimize the operations of robots that lack sensors.